Erosion wear at the bend of pipe during tailings slurry transportation: Numerical study considering inlet velocity, particle size and bend angle - Chen, Qiusong; Zhou, Hailong; Wang, Yunmin; Wang, Daolin; Zhang, Qinli; Liu, Yikai (International journal of minerals, metallurgy and materials, 2023)
Pipeline hydraulic transport is a highly efficient and low energy-consumption method for transporting solids and is commonly used for tailing slurry transport in the mining industry. Erosion wear (EW) remains the main cause of failure in tailings slurry pipeline systems, particularly at bends. EW is a complex phenomenon influenced by numerous factors, but research in this area has been limited. This study performs numerical simulations of slurry transport at the bend by combining computational fluid dynamics and fluid particle tracking using a wear model. Based on the validation of the feasibility of the model, this work focuses on the effects of coupled inlet velocity (IV) ranging from 1.5 to 3.0 m·s −1 , particle size (PS) ranging from 50 to 650 µm, and bend angle (BA) ranging from 45° to 90° on EW at the bend in terms of particle kinetic energy and incidence angle. The results show that the maximum EW rate of the slurry at the bend increases exponentially with IV and PS and first increases and then decreases with the increase in BA with the inflection point at 60° within these parameter ranges. Further comprehensive analysis reveals that the sensitivity level of the three factors to the maximum EW rate is PS > IV > BA, and when IV is 3.0 m/s, PS is 650 µm, and BA is 60°, the bend EW is the most severe, and the maximum EW rate is 5.68 × 10 −6 kg·m −2 ·s −1 . In addition, When PS is below or equal to 450 µm, the maximum EW position is mainly at the outlet of the bend. When PS is greater than 450 µm, the maximum EW position shifts toward the center of the bend with the increase in BA. Therefore, EW at the bend can be reduced in practice by reducing IV as much as possible and using small particles.